Assessment of access to first contact in the perspective of professionals - Glaucia Margarida Bezerra Bispo; Eduarda Maria Duarte Rodrigues; Amanda Cordeiro de Oliveira Carvalho; Kenya Waleria de Siqueira Coêlho Lisboa; Roberto Wagner Júnior Freire Freitas; Marta Maria Coelho Damasceno (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objectives: to evaluate the "access to first contact" attribute, from the perspective of Primary Care Health professionals. Methods: an evaluative and cross-sectional study, carried out from February to March 2017. The sample consisted of 163 health professionals, of both genders, who worked in the basic care of the Municipality of Juazeiro do Norte, Ceará. Access to first contact was evaluated by the Primary Care Assessment Tool (PCATool). The 6.60 mark was used as the cut-off point for the evaluated attribute. Results: access to first contact reached a score of 3.3, denoting a low degree of orientation for Primary Health Care. Nurses were the ones who evaluated the attribute more negatively (p=3.2). Conclusions: access to first contact obtained a low score, pointing to the fragility of the Family Health Strategy as a gateway to the Brazilian Unified Health System (Sistema Único de Saúde).